PEMBIAYAAN GADAI EMAS KONVENSIONAL DAN SYARIAH - Laily Nurhayati; Radjab Djamali (IAIN Manado, 2016)
Financing system used in gold pawn transactions in Indonesia are conventional and shar’i. Conventional system is employed only by pawnshops owned by the government, namely “Pegadaian”. Meanwhile,the sharia system is employed by sharia private banks, sharia business units, and sharia pawnshops. Gold mortgage finance at pawnshops is calculated based on the loan amount multiplied by interest multiplied the number of days. Meanwhile, gold mortgage finance at sharia pawnshops and sharia banks as well as Islamic business is calculated based on the estimated value (collateral/gold) multiplied by the interest multiplied by the number of days. The results obtained for the amount of financing (loans) is the same, but smaller nominal interest is obtained when it calculated using the Islamic system. However, the numberof shariadebtors is still very small compared to the conventional debtors.